Restructuring education activities for full online learning: findings from a qualitative study with Malaysian nursing students during COVID-19 pandemic - Romli, Muhammad Hibatullah; Foong, Chan Choong; Hong, Wei-Han; Subramaniam, Paramesevary; Wan Yunus, Farahiyah (BioMed Central, 2022)
The COVID-19 pandemic and Movement Control Order have restricted learning activities from traditional face-to-face classrooms attendance shifted to full online learning in the student’s environment. The present study is aimed to explore pertaining issues on full online learning among nursing students and offer a contingency solution. Nursing students from one Malaysian public institution were recruited. The sessions were conducted online via teleconference and were recorded. The data were analysed using thematic analysis with the assistance of QDA Miner Lite software. Twenty-one students participated, resulting in four focus group discussions and three in-depth interviews. Three themes with a total of ten sub-themes were generated: (i) Full online learning has ramifications on life (it is about life; blurred division on education life and personal life; non-conducive environment for learning; health and well-being; human is an adaptable being while the transition takes time), (ii) full online learning is a medium of teaching and learning delivery but with several concerns (the boon and bane of fully online learning; challenges associated with full online learning; coping strategy in handling full online learning), and (iii) Foundation in teaching and learning is the key (role of the educator; teaching and learning approaches; motivation and regulation). A model of practice for full online learning was developed, consisting of some modifications to create a conducive and healthy learning environment. This study embarks on a more structured and standard online learning practice for making the Internet of Things and Industrial Revolution 4.0 concept a contemporary and mainstream education practice.